Psychiatric symptoms in Salla disease - Aulanko Ida; Rahikkala Elisa; Moilanen Jukka (SPRINGER, 2025)
Salla disease (SD) is a rare lysosomal storage disorder characterised by intellectual disability ataxia, athetosis, nystagmus, and central nervous system demyelination. Although the neurological spectrum of SD's clinical phenotype is well defined, psychotic symptoms in SD remain unreported. We reviewed the presence of psychiatric symptoms in patients diagnosed with SD. Medical records of all SD patients at Oulu University Hospital during the years 1982-2015 were systematically reviewed to evaluate the presence of psychiatric symptoms. Psychiatric symptoms were frequently associated with SD (10/24, 42%), and two patients were described as developing psychosis as adolescents. We reported their clinical characteristics in detail and assessed the prevalence of psychiatric symptoms in a cohort of 24 patients. Other psychiatric factors associated with SD were sleeping disorders (8/24, 32%), aggressive behaviour disorders or restlessness (6/24, 25%), and off-label antipsychotic medication (4/24, 17%). This report expands the knowledge of the phenotypic spectrum of SD and demonstrates the importance of recognising the possibility of psychiatric symptoms, including psychosis, in persons with SD.